Case report: The presence of third-degree atrioventricular block caused by pulmonary embolism masquerading as acute ST-segment elevation myocardial infarction - Ma, Min; Liang, Shichu; He, Yong; Wang, Hua (Frontiers in Cardiovascular Medicine, 2023)
The typical clinical manifestations of pulmonary embolism (PE) are chest pain, tachypnea, and hemoptysis. In addition, syncope and myocardial injury markers increased are not uncommon.The typical electrocardiogram (ECG) changes with the feature of sinus tachycardia, right bundle branch block (RBBB), S1Q3T3 pattern, and/or precordial T-wave inversion.However, is a rarity presence of a third-degree atrioventricular block ( Ⅲ °AVB). Yet, it is easily misdiagnosed or missed even though it has one of the common causes of chest pain.